Visionary Learning in the Subjects of Islamic Education and Character Based on Idealism in Generation Z - Nur Khotimah; Fatah Syukur (Jurnal Hikmatuna, 2020)
The aim of this study was to find a visionary learning model for subject Islamic Education and Character (IE-C) to shape character. The application of visionary learning in IE-C based on idealism makes it possible to achieve learning objectives by achieving spiritual aspects with noble character, especially for Z generation. Hence, the educators are encouraged to integrate future competencies (4K) in all IE-C materials, so that they can optimize the potential of students' visionary intelligence that consists of SQ, EQ, IQ, and PQ. The research method used in this study is a descriptive analysis with qualitative approach The results of this study indicate that in visionary learning an educator tries to integrate faith and practice into all IE-C learning. This learning focuses on the habituation program and future motivation, thus encouraging the creativity of Z generation students to be critical, communicative and able to collaborate with their friends. So that, the growth of noble character in the students of Z generation, can be implemented and the results can be expected to be achieved.